The role of surface implant treatments on the biological behavior of SaOS‐2 osteoblast‐like cells. An in vitro comparative study. Issue 8 (17th January 2012) - Conserva, Enrico; Menini, Maria; Ravera, Giambattista; Pera, Paolo
Abstract Objectives The aim of this study was an in vitro comparison of osteoblast adhesion, proliferation and differentiation related to six dental implants with different surface characteristics, and to determine if the interaction between cells and implant is influenced by surface structure and chemical composition. Material and methods Six types of implants were tested, presenting four different surface treatments: turned, sandblasted, acid‐etched, anodized. The implant macro‐ and microstructure were analyzed using SEM, and the surface chemical composition was investigated using energy‐dispersive X‐ray analysis. SaOS‐2 osteoblasts were used for the evaluation of cell adhesion and proliferation by SEM, and cell viability in contact with the various surfaces was determined using cytotoxicity MTT assays. Alkaline phosphatase (ALP) enzymatic activity in contact with the six surfaces was evaluated. Data relative to MTT assay and ALP activity were statistically analyzed using Kruskal–Wallis not parametric test and Nemenyi‐Damico‐Wolfe‐Dunn post hoc test. Results All the implants tested supported cell adhesion, proliferation and differentiation, revealing neither organic contaminants nor cytotoxicity effects. The industrial treatments investigated changed the implant surface microscopic aspect and SaOS‐2 cell morphology appeared to be influenced by the type of surface treatment at 6, 24, and 72 h of growth. SaOS‐2 cells spread more rapidly on sandblasted surfaces. Turned surfaces showed the lowest cell proliferation at SEM observation. Sandblasted surfaces showed the greatest ALP activity values per cell, followed by turned surfaces (P < 0.05). Conclusions On the base of this in vitro investigation, differently surfaced implants affected osteoblast morphology, adhesion, proliferation, and differentiation. Sandblasted surfaces promoted the most suitable osteoblast behavior.